PROSPECTS FOR THE DEVELOPMENT OF THE FIELD OF NATURAL SCIENCE IN PRIMARY EDUCATION - Shamsitdinova Muxayyo Abduraximovna (Web of Journals Publishing, 2023)
This article considers the goals of developing the field of natural science in primary education. It studies current literature, analyzes existing methods, provides potential results, participates in a discussion on defined trends, and concludes with proposals for creating a more robust and effective curriculum for natural sciences in primary schools.
Keywords: Natural Sciences, Primary Education, STEM, Survey-based Learning, Practical Experiences, Improvement of Curriculum, Teacher Training.